COSTA RICA: SISTEMA AGROINDUSTRIAL DEL ARROZ ANÁLISIS SOCIOMÉTRICO - Calvo Coin, Otto (Universidad de Costa Rica, 2023)
The rice is indispensable in the basket of daily consumption of the Costa Ricans and, no another product substitutes it; but, the country produces only the 55% of the national consumption, aggravated by the industrial conflicts vis à vis producing. To study the system of the rice, in the first place models are built of social-diagrams, that permit a holistic perspective. In second place, these social-diagrams serve of base to build a matrix social-metrics, that estimated the social capital of the system, the leadership of the social actors and they quantify the feedbacks of information of the system. In third place a scene is built that reflect the present chaos of the system, which is compared with the previous model by hypothesis of a chi-square test. Finally an interpretation of the lobbies of power to be able is done.